Sengketa Harta Bersama: Tinjauan Yuridis atas Status Bangunan Menantu di Tanah Mertua - Muhammad Muhammad (IAIN Langsa, 2025)
This study examines the juridical status of buildings constructed by sons-in-law on land owned by their parents-in-law in Mesjid Tuha, Pidie Jaya Regency, a situation that frequently triggers disputes over marital property following divorce. The primary issue arises from the overlap of ownership rights and the lack of adequate administrative evidence, resulting from a culture of trust that often neglects formal legal documentation. This qualitative research employs a juridical-empirical approach and utilizes the interactive analysis model developed by Miles and Huberman. The findings indicate that, although the building is legally classified as marital property under the principle of horizontal separation, the son-in-law’s position remains highly vulnerable due to the absence of authentic financial documentation. In Mesjid Tuha, dispute resolution is more effectively achieved through Sulh (amicable settlement) or village-level customary mediation, which generally results in a financial compensation agreement based on the value of the building. This approach is considered the most maslahah (beneficial) because it safeguards the son-in-law’s economic rights without negating the parents-in-law’s ownership rights over the land, while simultaneously preserving family harmony. The study emphasizes the importance of asset documentation within marriage as an integral part of sound administrative governance in Islamic society.